The Research of Stakeholder Power Impact on Project Implementation - Artur Biskupek (Trendy Ekonomiky a Managementu, 2016)
Purpose of the article: The article show summarized information about stakeholders and their role in project implementation based on literature review. The second part of the article is dedicated for the research about stakeholder influence on project implementation. The only condition to participate in the survey was managing projects. Although the respondents are employed in the area of south Poland, they implement projects all over Poland. The research tool was a questionnaire which was sent by e-mail to the respondents. 90 project managers from the area of south Poland were invited to join the project, and 62 people sent back a completed questionnaire. Methodology/methods: The research was done by a questionnaire with twenty two question, which was divided into three parts. The first part was the imprint, which consisted of three questions. The second part consisted of two questions, which concerned the way of defining the word “stakeholder”. The third part concerned the topic of the research and consisted of seventeen questions. Scientific aim: The aim of the article is presenting the results of the research which was done, to show the research results of project stakeholder influence on the project implementation. Findings: The results received from the survey in the process of analysis and interpretation allow to put forward a thesis that stakeholders as a whole group are significant for the implementation of the whole project. Their impact is so important that it is possible to tell that they decide also about the project success or failure. Conclusions: The respondents show that stakeholders affect every area in large extent or very big extent. The fact has been proved in table 1 which shows the most frequently chosen answers by respondents. However, by conducted analysis by the standard deviation it is possible to see a large dispersion of the results.